Collective motion of pulsating active particles in confined structures - Wan-hua Liu; Wei-jing Zhu; Bao-quan Ai (New Journal of Physics, 2024)
The collective motion of pulsating active particles with periodic size contraction is investigated in a two-dimensional asymmetric channel. Our findings reveal that changes in particle size can act as a non-equilibrium driving force, disrupting the system’s thermodynamic equilibrium and leading to the transformation of self-contraction motion into directional motion in the asymmetric channel. The specific direction of motion is dictated by the symmetrical properties of the channel. Furthermore, our study identifies an optimal degree of channel opening (or self-pulsation frequency) at which the average velocity reaches its peak value. At lower frequencies, the average velocity demonstrates a peak function in relation to the self-pulsation amplitude (or particle number density). Conversely, at higher frequencies, the average velocity increases with the self-pulsation amplitude (or particle number density). The system exhibits three distinct states: the arrested ordered state, disordered state, and cycling ordered state. Notably, particle rectification reaches its optimum in the disordered state.